2007
DOI: 10.1128/jvi.02725-06
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CD4 by Human Immunodeficiency Virus Type 1 Nef Is Dependent on Clathrin and Involves Direct Interaction of Nef with the AP2 Clathrin Adaptor

Abstract: Nef, an accessory protein of human and simian immunodeficiency viruses, is a critical determinant of pathogenesis that promotes the progression from infection to AIDS. The pathogenic effects of Nef are in large part dependent on its ability to downregulate the macrophage and T-cell coreceptor, CD4. It has been proposed that Nef induces downregulation by linking the cytosolic tail of CD4 to components of the host-cell protein trafficking machinery. To identify these components, we developed a novel Nef-CD4 down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
262
2
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(294 citation statements)
references
References 81 publications
14
262
2
16
Order By: Relevance
“…As has been previously shown by yeast three-hybrid (Y3H) assays, the interaction of Nef with γ1-σ1A requires a conserved (D/E)xxxL(L/I) signal in Nef (i.e the ENTSLL 165 motif in HIV-1 NL4-3 Nef ), and a conserved basic residue in γ1 at position 15 (Arg 15 ) (Chaudhuri et al, 2007;Mattera et al, 2011) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…As has been previously shown by yeast three-hybrid (Y3H) assays, the interaction of Nef with γ1-σ1A requires a conserved (D/E)xxxL(L/I) signal in Nef (i.e the ENTSLL 165 motif in HIV-1 NL4-3 Nef ), and a conserved basic residue in γ1 at position 15 (Arg 15 ) (Chaudhuri et al, 2007;Mattera et al, 2011) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 89%
“…Instead, Nef accelerates the endocytosis of CD4 and targets the internalized molecules to the lumen of lysosomes for degradation (Aiken et al, 1994;Rhee and Marsh, 1994). To accomplish this, Nef directly binds the cytosolic tail of CD4 (Grzesiek et al, 1996;Preusser et al, 2001;Rossi et al, 1996) and the endocytic adaptor protein 2 (AP-2) (Chaudhuri et al, 2007(Chaudhuri et al, , 2009Doray et al, 2007;Lindwasser et al, 2008). This activity promotes the cooperative assembly of a tripartite Nef-AP-2-CD4 complex (Chaudhuri et al, 2009;Ren et al, 2014) that induces the endocytosis of CD4 mediated by clathrin-coated vesicles (CCVs) (Burtey et al, 2007;Greenberg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that acidic dileucine signals bind to members of the clathrin-associated heterotetrameric adaptor protein family (Bonifacino and Traub, 2003;Janvier et al, 2003;Chaudhuri et al, 2007;Doray et al, 2007). The acidic dileucine signal in Tyr mediates an interaction with both AP-3 and AP-1 (Honing et al, 1998;Theos et al, 2005), whereas the corresponding signal in Tyrp1 has been shown to interact with AP-1 only (Theos et al, 2005).…”
Section: Oca2 Binds Adaptors Ap-1 and Ap-3 In A Dileucinedependent Mamentioning
confidence: 99%